STRENGTHENING HALAL MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMEs) WITHIN THE ISLAMIC ECONOMY: A DESCRIPTIVE QUALITATIVE ANALYSIS OF CHALLENGES, OPPORTUNITIES AND POLICY IMPLICATION IN INDONESIA - Syeima Nadhira (PT. Samudra Solusi Profesional, 2024)
The halal economy has emerged as one of the fastest-growing segments of the global economic system, driven by the expansion of Muslim populations, increasing awareness of halal standards, and the ethical dimensions of Islamic consumption. Indonesia, as the country with the largest Muslim population in the world, possesses substantial potential to position itself as a global hub for halal products and services. This article aims to examine the role of halal-oriented micro, small, and medium enterprises (MSMEs) in strengthening Indonesia’s Islamic economy through a descriptive qualitative approach based on secondary data. The study relies on a systematic review of academic literature, policy documents, and official statistical publications, particularly from Badan Pusat Statistik (BPS), Badan Penyelenggara Jaminan Produk Halal (BPJPH), and international halal economy reports. The findings indicate that MSMEs play a strategic role in the halal economy, particularly in the food and beverage sector, which dominates halal consumption. However, several structural challenges persist, including limited awareness and understanding of halal standards, administrative and financial barriers to halal certification, and weak integration into halal value chains. Despite these constraints, significant opportunities are evident in the form of strong domestic demand, supportive regulatory frameworks, and growing global halal markets. The study highlights the importance of policy coherence, capacity-building programs, and collaborative ecosystem development to enhance MSME participation in the halal economy. This article contributes to the literature by providing a comprehensive synthesis of empirical and policy-based evidence on halal MSMEs and offers practical implications for policymakers and stakeholders seeking to strengthen Islamic economic development in Indonesia.